Analisis Keberagaman Karyawan dalam Meningkatkan Kreativitas dan Inovatif Terhadap PT. Tiara Teluk Jaya - Arfiansyah Adhami N; Aura Cantika; Bhayu Kurniawan; Faiza Andiva; Vivi Nila Sari (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
This Community Service (PKM) activity aims to find out and increase the owner's understanding and knowledge of how to assess performance in developing product innovations to support competitive advantages. The diversity of employees at PT. Tiara Teluk Jaya has a big influence in increasing creativity and innovation. This research aims to find out how much influence diversity has in increasing creativity and innovation. This research focuses on employee diversity carried out by PT. Tiara Teluk Jaya to increase employee effectiveness and innovation. Judging from the customs and culture that exist in Indonesia, there is a lot of diversity that has a broader perspective in dealing with problems and finding new and creative solutions. The analytical methods used are interviews, observation and data collection. Based on the results of observations and interviews conducted by researchers, the influence of diversity on creativity and innovative employee performance has a significant impact. There is a positive and significant influence between creativity and innovation and employee performance.